IMPLEMENTASI TOLERANSI BERAGAMA DI PONDOK PESANTREN DARUT TAQWA PASURUAN - Rahmawati, Erik Sabti; Satria, M. Hatta (De Jure: Jurnal Hukum dan Syari'ah, 2014)
This  Research  was aimed  to determine the construct and  implementation  of the concept of religious tolerance in Darut Taqwa boarding school Pasuruan led by Kyai Sholeh  Bahruddin. This study used a qualitative method with a phenomenological approach, whereas the method of  data collection used  in-depth interviews and documentation. The results of this study showed that: Construct of Kyai Sholeh thought about pluralism and religious tolerance, which is also the foundation for the policy programs at Darut Taqwa boarding school, can be categorized in the inclusive of thought and  attitude, which is believe in the existence of truth and salvation  of other religions but the highest safety standards of truth remain in their own religion. Kyai Sholeh while promoting the truth of Islam as a religion, but He did not reduce its respect for other religions  and not be an impediment to establishing religious tolerance in public life.  Kyai  Sholeh  thought  of religious tolerance is also well applied in  His policies  in managing the boarding school and formal education institutions, which is able to be a reflection of Islam and Islamic  boarding school which are inclusive and rahmatan lil alamin.